Dampak Efisiensi Renovasi Lapangan Merdeka Medan terhadap Perkembangan UMKM Lokal - Alvian Manaralom Siregar; Kurnia Simbolon; Khairani Aprilia; Queen Helen Br. Bukit; Rohani Rohani; Elsa Kardiana (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This journal discusses the efficiency impact of the renovation of Merdeka Field on the development of local MSMEs. The aim is to understand and analyse the multifaceted impacts that the renovation of Merdeka Square has had on the development of local MSMEs, as well as to identify and assess the various challenges faced by local MSMEs following its revitalization, including issues relating to accessibility and the potential commercialization of public spaces. The methodology used in this study involved direct observation of MSME activities both before and after the renovation. In addition to comprehensive interviews with MSMEs and relevant stakeholders, in addition to documentation related to the revitalization process of Merdeka Square and its impact on MSMEs. With well-defined regulations and an enhanced suite of facilities, MSMEs near Merdeka Square are poised to achieve superior development and maintain competitiveness amidst the evolving urban landscape.